Potential Effect of Bay Leaf (Syzygium polyanthum [Wight] Walp.) Essential Oil for Herbal Toothpaste Active Agent - Mutiara Annisa; Harsini Harsini; Yosi Bayu Murti (Majalah Obat Tradisional, 2022)
Bay leaf is a herbal plant containing essential oil with antioxidant activity. Antioxidant effects give bay leaf essential oil ability as a toothpaste active agent. This research aim is to evaluate the chemical composition and antioxidant activity of bay leaf essential oil to find out the potential as toothpaste active agents. Bay leaf used in this research was taken from Lendah, Kulon Progo in the evening. Steam-hydrodistillation is conducted and chemical composition is analyzed using the GC-MS method. The Antioxidant activity test is conducted with DPPH and FRAP methods. Toothpastes were formulated with three concentrations of bay leaf essential oil (0.125%, 0.25%, 0.5%). Stain prevention test using formulated toothpastes, no active agent toothpaste (negative control), and commercial toothpaste (positive control) was conducted on 20 bovine teeth to obtain the value of colour change (ΔE) before and after the experiment, then analysed using one-way ANOVA parametric test (CI 95%). The chemical composition of bay leaf essential oil detected using GC-MS showed 29 compounds. The highest percentages are cis-4-decenal (37.87%), Decanal (16.73%), and octanal (16.63%). IC50 value from DPPH and FRAP method are 2.079µg/mL and 3.277µg/mL. One-way ANOVA test showed there was an effect from bay leaf essential oil as stain prevention toothpaste active agent. Bay leaf essential oils toothpastes have no significant difference in ΔE value to positive control toothpaste. The conclusion of this research is bay leaf essential oil contains aldehyde compounds in high percentage which provides a very high antioxidant effect. Bay leaf essential oil is the potential to be used as a toothpaste active agent.